SOCIALIZATION OF THE USE OF WEBSITE APPLICATIONS ABOUT THE MOST DISEASES AT HARAPAN RAYA PUSKESMAS - Handoko, Bobi; Asep Marzuki; Sherly Mutiara (J-COSCIS : Journal of Computer Science Community Service, 2025)
Health centers are government agencies in public health development services. It is difficult to find the highest disease in several health centers in the city of Pekanbaru. Many health centers still use manual records and systems that are not well integrated. This application is designed to provide accurate and up-to-date information about the highest disease in the region. With this application, it can make it easier for people to get information quickly and up to date. The search for the highest disease is integrated with technology, making it easier for people to access this service. Methods Community service activities by socializing the use of the highest disease application to community groups in Pekanbaru City. The results of this counseling are to provide information to the community and how to use the application inputted by the puskesmas on the website about the highest disease in the working area of the Pekanbaru City Health Office.